Case Report: Three novel pathogenic ABCC2 mutations identified in two patients with Dubin–Johnson syndrome - Zhao, Chenyu; Shi, Xiaoliu; Zhang, Yonghong; Huang, Hui (Frontiers in Genetics, 2022)
Background: Dubin-Johnson syndrome is a rare autosomal recessive genetic disease, which is caused by mutations in the ABCC2 gene. It is characterized by chronic hyperbilirubinemia. Here, we reported two pedigrees affected with Dubin-Johnson syndrome, which were caused by three novel pathogenic ABCC2 mutations. Case summary: The two patients exhibited intermittent low-grade predominantly conjugated hyperbilirubinemia and showed no other abnormalities. They were diagnosed clinically as Dubin-Johnson syndrome. Three novel pathogenic ABCC2 mutations, c.2980delA, c.1834C>T and c.4465_4473delinsGGCCCACAG, were identified by the whole-exome sequencing. These mutations could be responsible for Dubin-Johnson syndrome in the two pedigrees. The genetic test confirmed their diagnosis of Dubin-Johnson syndrome. Conclusions: These results contributed to the genetic diagnosis of the two patients with Dubin-Johnson syndrome, and expanded the variant database for the ABCC2 gene.